Fatwa-fatwa M. Quraish Shihab dalam Bidang Hukum Islam - Mursalim, Mursalim; Madani, Abu Bakar (LP2M IAIN Samarinda, 2013)
This study wanted to see about legal thought of Shihab in one of his book that discuss the issues of Islamic law ,